2001
DOI: 10.1021/jp010754f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Potential Structures of Heat-Treated Single-Wall Carbon Nanohorn Assemblies

Abstract: The microporosity of the heat-treated single-wall carbon nanohorn (SWNH) particles is characterized by nitrogen adsorption at 77 K and the molecular potential calculation using the function, which is based on the Lennard-Jones pair potential. The depth difference of the molecular potential for N 2 between the SWNH intraparticle pore and the interparticle space is close to 1000 K. Although the SWNH without the heattreatment has no open intra-nanohorn space, the intraparticle pores open with the high-temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
138
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 156 publications
(145 citation statements)
references
References 27 publications
5
138
0
1
Order By: Relevance
“…[15] Earlier results also showed that heat treatment of SWNHs in O 2 at 693 K opens the SWNHs almost perfectly, and a micropore volume of 0.47 mL g ±1 and a specific surface area of 1010 m 2 g ±1 were obtained. [16] This result suggests that there is a limitation in microporosity enhancement by only opening the nanohorns. Therefore, it is necessary to control the interstitial pores as well as internal pores, in order to obtain more highly microporous SWNH assemblies.…”
mentioning
confidence: 99%
“…[15] Earlier results also showed that heat treatment of SWNHs in O 2 at 693 K opens the SWNHs almost perfectly, and a micropore volume of 0.47 mL g ±1 and a specific surface area of 1010 m 2 g ±1 were obtained. [16] This result suggests that there is a limitation in microporosity enhancement by only opening the nanohorns. Therefore, it is necessary to control the interstitial pores as well as internal pores, in order to obtain more highly microporous SWNH assemblies.…”
mentioning
confidence: 99%
“…To avoid the aggregation, we loaded ZnPc onto SWNHox, a novel drug carrier. SWNHox is graphitic tubule with a diameter of 2-5 nm and lengths of 40-50 nm (2) that have a relatively large inner space (24,25) suitable for carrying drugs. Thousands of SWNHox partially coalesce to form an 80-to 100-nm spherical aggregate (2), and this aggregate is expected to have enhanced permeability and retention properties (26,27) that make SWNHox effective for passive delivery of drugs to tumors.…”
mentioning
confidence: 99%
“…Figure 10 shows the interaction potential profiles of SWCNT with CH4 and H2 using moleculenanopore interaction potential using the established potential functions for carbon cylinder of an infinite length. (Tjatjopoulos et al 1988;Murata et al 2001). …”
Section: Nanoscale Curvature Sign Dependence Of Interaction Potentialmentioning
confidence: 99%